Exploring the contribution of professional staff to student outcomes: a comparative study of Australian and UK case studies. Issue 6 (1st November 2016) - Graham, Carroll; Regan, Julie-Anne
ABSTRACT: This paper reports on the second stage of a comparative study between two higher education institutions: one in Australia and the other in the United Kingdom, which explored the contributions of professional staff to student outcomes. The first stage acted as a scoping exercise to ascertain how the contributions of professional staff to student outcomes could be investigated. The second stage of the study aimed to undertake a more in-depth exploration of self-reported behaviours in a range of professional staff roles, within the two case studies. The main finding of the comparative study is the broad similarities between the case studies, in self-reported behaviours that contribute to successful student outcomes. Four key factors were identified, which enable or inhibit the contributions of professional staff to successful outcomes. Three of the four factors were found to be the same in both case studies, whereas technology was more important in the Australian case study.